Laws and Ordinances Governing the City of Chicago 78 (Murray F. Tuley ed., 1873) - (:unkn) unknown (My University, 1866)
Chapter 28-Misdemeanors, § 15-Fire Arms and Fire-Works Not to be Discharged-Permission-Penalty. Revised Ordinance of 1866: Prohibited firing or discharging any cannon, gun, fowling piece, pistol, or firearms of any description, or fire, explode, or set off any squib, crackers, or other thing containing powder, or other combustible, or explosive material. Violators shall be fined not less than two nor more than five dollars.
Keywords: DISCHARGE